Integration of Risk Strategy of PT Bukit Asam, Tbk Subsidiaries - Boni Susanto; Oktofa Yudha Sudrajad (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Risk management in State-owned enterprise (SOEs) in Indonesia presents difficulties from operational risks to regulatory complexity. SOEs that have subsidiaries, such as PT Bukit Asam Tbk (PTBA) struggle with the effective implementation of structured and comprehensive risk management frameworks. This research aims to identify and propose a precise method for developing a risk strategy (Risk Capacity, Risk Appetite, Risk Tolerance, and Risk Limit) that can be integrated from the SOE holding company to its subsidiaries, and to strengthen the risk management framework's resilience for reliable and efficient implementation. The methodology employing quantitative followed by qualitative approach and stick to Indonesian Ministry of SOEs guidelines (PERMEN BUMN PER-2/MBU/03/2023 and SK-6/DKU.MBU/10/2023). Independent variables influencing the framework include financial metrics (NWC, Retained Earnings, NOPAT), regulatory requirements, and best-practice allocation models (equity-based, profit-based, asset-based). The dependent variable is the successfully integrated and defined risk strategy for the holding and its subsidiaries. Data includes financial reports of subsidiaries of a major Indonesian SOE for the 2019-2023 period, alongside qualitative data from Focus Group Discussions (FGDs) and questionnaires. Results for a representative subsidiary indicate a NOPAT-based Risk Capacity of 102.000 million rupiah, a Risk Appetite of 17% of Risk Capacity, and Risk Tolerance of 18.7%. The equity-based Risk Limit distribution method yielded 2.838 million rupiah, differing from SK-6/DKU.MBU/10/2023 calculations with comparisons with Altman Z-Score.